Cunning and Tricks Against the Heirs of the Inheritance: Erbil Governorate as an Example (Raparin Journal of Humanities (RJH), 2025)
This study aims to illustrate some cunning and tricky practices in some Muslim societies - the province of Erbil as a model– performed by some weak souls to prevent beneficiaries from the heirs. This is all because those deceitful people attempt to satisfy their own desires and do not fear Almighty. The study consists of an introduction, a preface, two sections, and a conclusion. The first section explains deceitful practices and tricks against the heirs, based on real and authentic problems facing people in everyday life. The second section is divided into two sub-sections one of which examines deception and tricks against female heirs, including giving them a small amount of the inheritance, encouraging them to abandon their share, perhaps preventing them from inheriting because of some bad habits, or claiming that the woman may mismanage spending money and other deceptions and tricks. The second sub-section is devoted to deception and tricks in the commandments, such as implementing the commandments that are contrary to the Sharia, and the lack of justice in the bequest of inheritance funds, or claiming that each of the heirs is the guardian of the others. The conclusion shows the findings of the study, followed by the list of the references.